Smoking Behavior in First-year Medical Students at the University of Medical Sciences of Cienfuegos - Yoel Hernández Guerra; Alain Rodríguez Gómez; Ignacio Marrero Silva; Carlos Manuel Mora Hernández; Zulema Tamara Mesa Montero (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
Background: smoking has become one of the biggest problems of international Public Health. The World Health Organization reports smoking as the leading preventable cause of disease, disability, and premature death. When said consumption begins in early adolescence, it favors the consolidation of the smoking habit, which extends into adulthood. Objective: to characterize the behavior of smoking in first-year medical students at the University of Medical Sciences of Cienfuegos. Methods: a descriptive, cross-sectional study was carried out in first-year medical students at the University of Medical Sciences of Cienfuegos in the period from September 5, 2018 to July 20, 2019. The universe consisted of 199 students and the sample was made up of 61 of them. The variables: age, sex, skin color, start of consumption, causes that motivated smoking and place of consumption were studied. Absolute frequencies and percentages were used as statistical methods. The results were presented in statistical tables. Results: 30.5 % of adolescents are smokers and 85.24 % are female. The 18-year-old group predominated, with 67.21 %. 77.0 4 % started smoking after the age of 16 and 100 % smoke in public places. Conclusions: there was evidence of an increase in the smoking habit in adolescents at the expense of the female sex, whose habit began at an early age.